Anti-aging mechanism and rheological properties of lignin, quercetin, and gallic acid as antioxidants in asphalt. (10th March 2023) - Sun, Lijun; Gu, Xingyu; Hu, Dongliang; Zhou, Zhou; Wang, Guoliang
Highlight: Phenolic hydroxyl H atoms are easily attracted to react with O2 to prevent asphalt aging. The antioxidant activity of quercetin and gallic acid is stronger than that of lignin. Three modifiers improve the resistance of asphalt binder to permanent deformation. The dosage of three modifiers has a negative effect on the fatigue life of the asphalt. Abstract: Lignin has attracted attention as an antioxidant in asphalt. To guide the improvement of the anti-aging activity of lignin, we investigated the mechanism whereby lignin acts as an asphalt antioxidant to inhibit asphalt aging by combining density functional theory and laboratory test methods. We then identified the factors affecting the antioxidant activity of lignin through comparisons with quercetin and gallic acid, which are highly active phenolic anti-aging agents. Finally, the effects of lignin, quercetin, and gallic acid as antioxidants on the rheological properties of asphalt binders were investigated. It was discovered that in lignin, quercetin, and gallic acid molecules, the phenolic hydroxyl H atom can not only be picked up quickly but also has a high positive electrostatic potential around it. Thus, these molecules are easily attracted to and react with O2 or HO2, thereby preventing asphalt aging. Quercetin and gallic acid have more phenolic hydroxyl groups than lignin, resulting in stronger antioxidant activity, which is consistent with experimental results. Therefore, we suggest increasing the phenolic hydroxyl content and reducing the molecular weight of lignin via structural modification to enhance its anti-aging activity. Additionally, the resistance of asphalt binders to permanent deformation, elastic recovery, and fatigue resistance were improved by the addition of lignin, quercetin, and gallic acid. Increasing the amount of admixture can further improve the first two properties but can significantly reduce the fatigue life of the asphalt binder.